Estudo comparativo de vias de acesso cirúrgico na contracepção cirúrgica feminina: Microlaparoscopia versus minilaparotomia - Modotte, Waldir Pereira [UNESP]; Dias, Rogerio [UNESP]; Frei, Fernando [UNESP]; Dias, Daniel Spadoto [UNESP]; Fernandes, Flávio Ferreira [UNESP] (FapUNIFESP (SciELO), 2006)
Purpose: to compare in a retrospective way, 51 women who underwent tubal ligation, 30 through microlaparoascopy (Gmicrol) and 21 through minilaparotomy (Gminil). Methods: the analyzed parameters were: total time for accomplishment of the procedure and the surgical technique, time of hospital stay and return to the habitual activities after the surgery, postoperative pain, morbidity, satisfaction degree and esthetic effect, considering values of p<0,05 as significant, and also standard cost. Results: Gmicrol took less time to accomplish the surgery than the Gminil (43 against 57 minutes respectively, p<0,05), less time to accomplish the surgical technique (6.48 against 30.32 minutes respectively, p<0,05), and lower hospital stay (9,90 hours as against 41,7 hours respectively, p <0,05). There was no significant difference between the two groups regarding time to return to the habitual activities after surgery. To evaluate postoperative pain, a scale of 0-10 it was applied. Gmicrol present a lower pain score on the 1st and 2nd postoperative days (1.13 and 0.26 to Gmicrol and 4.52 and 1.14 to Gminil, respectively, p<0,05). There was no significant difference between immediate postoperative the most common complaint being pain at the site of pain and that on the 3rd postoperative day. Gminil presented a higher morbidity rate incision. To evaluate the satisfaction degree and esthetic effect, numeric values were attributed to as good, regular, poor and very bad as answered by the patiets. Gmicrol presented a higher satisfaction degree (p<0,05) and better esthetic effect as compared to Gminil (p <0,05). The microlaparoscopy standard cost was R$ 109.30 being lower than that of minilaparotomy. Conclusions: tubal ligation by microlaparoscopy, under local anesthesia and conscious sedation presented some advantages compared to minilaparotomy.
Comparative study of female surgery contraception access: Microlaparoscopy versus minilaparotomy
Keywords: Contraception; Laparoscopy/methods; Laparotomy/methods; Retrospective studies; Sterilization; Tubal/methods